Challenges of the COVID-19 Pandemic: Experiences from South Korea and Taiwan. (March 2023) - Wang, T.Y.
The coronavirus, also known as COVID-19, has dramatically disrupted the global community, causing more than 6 million deaths worldwide and changing daily lifestyles for billions. Two Asian countries, South Korea and Taiwan, have been able to maintain low rates of infections and fatality. Five articles are collected in this special section to examine their successful experiences and the challenges they faced.